IMPLEMENTASI PROGRAM BINA PRIBADI ISLAMI (BPI) DALAM MEMBENTUK AKHLAK ISLAMI SISWA KELAS 6 DI SDIT AL-AZKAR PAMULANG - Karima, Litakuna; Ainun Aliya Sakinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of declining student morality observed within the school environment, as reflected in inappropriate behavior and a lack of social awareness. This issue is influenced by environmental factors as well as the impact of technological advancement and globalization on students' lives. SDIT Al-Azkar has developed a special initiative called the Islamic Character Development Program (Bina Pribadi Islami/BPI), which is designed to cultivate students' moral values through Islamic-based activities. The purpose of this study is to explore how the BPI program is implemented, as well as to identify the supporting and inhibiting factors that affect its execution. This study employs a qualitative research method. The data sources consist of the school principal, two teachers, and two sixth-grade students. Data collection techniques include interviews, observation, and documentation. The data analysis technique involves data reduction, data presentation, and drawing conclusions. The results of the study indicate that the BPI (Bina Pribadi Islami) program at SDIT Al-Azkar Pamulang has proven effective in shaping students’ Islamic character holistically across cognitive, affective, and psychomotor domains. This effectiveness is supported by curriculum planning activities, scheduling, and material preparation, followed by implementation through BPI subjects using the halaqah system, morning motivation and character reinforcement, and habituation of Islamic values such as congregational prayer, Qur’an recitation and review (tadarus/murajaah), fasting on Mondays and Thursdays, regular charity (infaq), Islamic studies sessions, and overnight spiritual activities (Mabit) for sixth-grade students. These activities aim to strengthen the students’ relationship with Allah SWT and help them internalize character and worship values that can be applied both in and outside of school. Furthermore, the program includes weekly Mutabaah evaluations to monitor students’ activities at home, fostering collaboration between the school and parents in shaping students’ character both at school and at home. Through the BPI program, students are trained to consistently apply Islamic values in their daily lives. Supporting factors include the involvement of teachers and parents, adequate facilities, and a conducive environment. Inhibiting factors include limited parental support, excessive use of gadgets, and social media distractions.